Issues Concerning Ways to Optimize the Electrothermal Induction Systems using Informational Techniques - Teodor LEUCA (Journal of Electrical and Electronics Engineering, 2009)
This paper presents some aspects of theelectromagnetic induction systems related to thepossibility of optimizing the processes and devices usedfor the induction heating through informationaltechniques. We have analyzed the specific problems ofthe power supply installations for an inductor –product system, as the electrical energy conversionaccording to specific and optimal parameters of theinduction heating process. The electromagneticinduction devices must be designed through thecoupled numerical modeling of the circuit inverter andof the induction heating process because the product’sproperties and the electrical parameters of the heatingdevice vary according to temperature. These methodstogether with the informational techniques aresignificantly improving the process: there are fewersuperior disturbance harmonics, fewer losses of thestatic commutation elements during the commutationprocess, the uniform lengthwise heating of the semifinishedproduct.